Emeritus Professor Reginald Paul (Reg) Coutts (1949–2021) - Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2021)
This obituary celebrates the many contributions of Emeritus Professor Reg Coutts (1949–2021) to telecommunications, to ICT innovation and to the Australian industry associations in which he had key leadership roles. The article quotes comments from many of Reg’s co-workers at different stages of his multi-faceted career.